Die trying [compact disc, unabridged] - Child, Lee; McClain, Johnathan, 1970- (Child, Lee. Jack Reacher novel, 2016)
When a woman is kidnapped off a Chicago street in broad daylight, Jack Reacher is in the wrong place at the wrong time. He is kidnapped with her. Chained together and racing across America toward an unknown destination, they're at the mercy of a group of men demanding an impossible ransom ... because Reacher's female companion is worth more than he imagines.With the FBI on the kidnappers' trail and under the impression that Reacher is one of the bad guys, Jack has to save himself and his mysterious companion--from the inside out--or die trying.